Assessment of venom variation and phylogenetic relationships of Micrurus dumerilii from three different regions of Colombia - Rey Suárez, Paola (2025)
In the Americas, the genus Micrurus (coral snakes) includes the highest number of snake species, andColombia is the second country with the greatest species diversity. Micrurus dumerilii has wide distributionand clinical importance in the country. The variability of its venom has not been extensivelystudied, and this could have implications for the neutralization by antivenoms. In this study, weexplored the phylogenetic relationships between specimens from three regions of Colombia (Antioquia,Chocó, and Santander) and the variation in their venoms using proteomics, in vitro and in vivo assays,and assessment of antigenic recognition by the anticoral-INS antivenom. Phylogenetic analyses usingnd4, Cyt b, and 16S rRNA gene fragments showed a close relationship between M. dumerilii from Ecuadorand Chocó (Colombia), and within the M. dumerilii clade, a particularly close relationship betweenspecimens from Antioquia and Santander. The venoms of M. dumerilii showed high overall similarity intheir chromatographic profiles, with peaks corresponding to the three-finger toxin (3FTx) and phospholipaseA2 (PLA2) protein families being predominant. Some differences were observed in the numberof protein families identified in each venom, but the main fraction responsible for lethality in thevenoms from Antioquia, Chocó, and Santander was preserved. The commercial antivenom available inColombia recognizes venom from all three regions. These general antigenic similarities between samplessuggest that it may not be necessary to include M. dumerilii venoms from different geographic areasas immunogens for the production of antivenom against this species.